The Strategies of Ajengans in Mediating Islam and Local Traditions in Rural West Bandung Regency - Mohammad Taufiq Rahman; Paelani Setia; Asep Iwan Setiawan (Jurnal Iman dan Spiritualitas, 2023)
Islam is not present in a society empty of culture but is here to find local traditions that develop and run amid a pluralistic society so that local traditions are maintained and packaged with Islamic values. Among the local traditions still growing in the community is "incense-burning", a routine Friday night ceremony and a part of the agricultural process in Lembur Sawah Hamlet, West Bandung Regency. Using interview and observation techniques, this qualitative research described local religious leaders (ajengan) as cultural intermediaries between Islam as a world religion and local beliefs.The figures Ajengans referred to in this article are the Kiais (Islamic scholars) of Pesantren (Islamic boarding school) who influenced society; they had merged into Nahdlatul Ulama, culturally and structurally. The results showed that the community understood local traditions as shari'a that must be followed. Therefore, they represented the "sunnah of their ancestors," even though they did not understand the symbolic meaning of the tradition. Here, the religious scholars of Islam played a role in straightening existing traditions combined with traditions with Islamic nuances, namely, incense-burning activities in tahlilan, Yasinan, khotmil Qur'an, shahriahan, and manakiban events. Also, the ajengans played a role as role models. Finally, the primary function of ajengans was to preserve existing traditions as part of a willing attitude toward local culture. Here, they modified deviant local traditions with Islamic nuances that did not violate the Islamic creed.